PREVALENCE OF DOMESTIC INTIMATE PARTNER VIOLENCE AMONG SELECTED CEBUANO WOMEN AND ITS RELATIONSHIP TO THEIR DEMOGRAPHICS - Ma. Magdalena C. Cataraja, Crizarah L. Guisadio, Shavy I. Abella, Mary Alwina S. Tabasa, Jelyn L. Cabague, and Ronald C. Yrog-Irog (Chelonian Research Foundation, 2024)
Abstract - Women often feel pressured to be married as one of the “toxic Filipino cultures” which includes not preparing them for realistic marital and familial problems that could arise, especially concerning domestic intimate partner violence. This research paper aims to determine the existence of a relationship between selected Cebuano women’s demographics and forms of domestic intimate partner violence (DIPV) from three (3) cities in Cebu: Cebu City, Mandaue City, and Lapu-Lapu City utilizing descriptive correlational survey design. Using Haj-Yahia's Questionnaire of Violence Against Women, ninety-nine (99) respondents gave consent to participate and answer the survey. The results found that the most prevalent form of abuse is physical abuse and the only demographic that has a relationship to the forms of abuse is selected Cebuano women’s educational attainment and its relation to sexual and economic abuse. These findings were analyzed with the use of descriptive statistics, frequency distribution, and chi-square. The implications of this study are significant to policymakers to show immediate action, future researchers to encourage them to research more on DIPV in the Philippines, and to other young women to be aware of DIPV.